Marshalling a Splintered Society: Censorship, Publicity and Propaganda in South Africa During the Second World War (Historia, 2022)
This article examines several important aspects of state propaganda in South Africa during the Second World War, the country’s participation in which was riddled by controversy. The wartime government of General J.C. Smuts lacked broad-based support and contested opposition which was shaped by Nazi influences. Latent South African socio-political friction surfaced, and anti-war violence ensued. In response, the Smuts administration adopted a multi-media publicity and propaganda campaign aimed at mobilising support for its war policy. The article focuses on subversive Nazi efforts within South Africa before and during the war, and on the impact of these on internal political divisions. These are significant because they formed the context for propaganda strategies formulated by the South African authorities. The article also analyses the ways in which the Smuts government deployed propaganda through its direction and censorship of radio, film and the print media, including the creation of a Bureau of Information. It argues that in the long run, state propaganda had limited effect and was ultimately a futile exercise as persistent realities, notably, racial prejudice, socio-economic privation and diverse political loyalties undermined the endeavour to achieve national cohesion and unity.
Keywords: Second World War; Censorship; radio; film; print media; propaganda; Bureau of Information; Smuts; Nazism